The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1177/2325967115570848
|View full text |Cite
|
Sign up to set email alerts
|

Biceps Tenotomy Versus Tenodesis in Active Patients Younger Than 55 Years

Abstract: Background:Proximal biceps pathology is a significant factor in shoulder pain. Surgical treatment options include biceps tenotomy and subpectoral biceps tenodesis. Tenotomy is a simple procedure, but it may produce visible deformity, subjective cramping, or loss of supination strength. Tenodesis is a comparatively technical procedure involving a longer recovery, but it has been hypothesized to achieve better outcomes in younger active patients (<55 years).Hypothesis:This study investigated the outcomes of youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
78
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 29 publications
6
78
0
Order By: Relevance
“…It has been reported that LHBT tenotomy and LHBT tenodesis achieve satisfactory efficacy. As compared with LHBT tenodesis, pure LHBT tenotomy has the advantages of simplicity, short surgery time and rapid post-operative recovery (21,32,33), but it may cause complications including Popeye sign deformity (21,24,25,28), upper arm spastic pain, loss of stability of the humeral head (34)(35)(36) and reduced forearm supination strength (20,22,23). LHBT tenodesis is a more invasive surgical procedure, but it maintains the length and tension of the original tendon and the strength of the elbow muscle, effectively prevents muscle atrophy and minimizes spastic and Popeye sign deformity in the upper arm (37,38).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that LHBT tenotomy and LHBT tenodesis achieve satisfactory efficacy. As compared with LHBT tenodesis, pure LHBT tenotomy has the advantages of simplicity, short surgery time and rapid post-operative recovery (21,32,33), but it may cause complications including Popeye sign deformity (21,24,25,28), upper arm spastic pain, loss of stability of the humeral head (34)(35)(36) and reduced forearm supination strength (20,22,23). LHBT tenodesis is a more invasive surgical procedure, but it maintains the length and tension of the original tendon and the strength of the elbow muscle, effectively prevents muscle atrophy and minimizes spastic and Popeye sign deformity in the upper arm (37,38).…”
Section: Introductionmentioning
confidence: 99%
“…Both techniques are viable options with their respective risks and benefits. In fact, the literature has indicated both procedures to produce favourable clinical results in adults 25. Therefore, selection criteria should be driven by the surgeon’s experience and the patient’s desires.…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes are comparable to those reported in recent studies on younger patients with persistent pain having been reported in up to 50% of patients. [25,26].…”
Section: Discussionmentioning
confidence: 99%